Manajemen Kualitas Air Dengan Teknologi Bioflok: Studi Kasus Pemeliharan Ikan Lele (Clarias Sp.) - Nadya Adharani; Kadarwan Soewardi; Agung Dhamar Syakti; Sigid Hariyadi (Jurnal Ilmu Pertanian Indonesia, 2016)
Biofloc technology is one of the alternative to overcome the problem of water quality of cultivation environment which was adapted from conventional waste management techniques. The purpose of this study was to assess the young catfish culture by applying bioflocs of some consortium products, such as Bacillus megaterium (BM), Supernit (SP), Depok 165 (DP165), Kayajaga (KJ) compared to non biofloc application for improving the water quality. The results of this study and statistical test showed that the lowest concentration of TAN by probiotic KJ was about 2.56 mg L-1, while the control was about 5.47 mg L-1, and the consortium of bacteria gave effect to  TAN value (p<0.05). The Lowest concentration of amonia by probiotic KJ was about 0.0001853 mg L-1, while control was about 0.0003973 mg L-1, and the consortium of bacteria did not give effect to amonia value (p>0.05). The lowest concentration of nitrite by probiotic BM was about 0.065 mg L-1, while the control  was about 0.124 mg L-1, and the consortium of bacteria gave effect to the nitrite value (p<0.05). The lowest concentration of nitrate by probiotic BM was about 1.203 mg L-1, while the control was about 3.437 mg L-1, and the consortium of bacteria gave effect to the nitrate value (p<0.05). Consortium of bacteria gave effect to the COD value (p<0.05), but all bioflocs treatments had an average value of COD higher than the control. The conclusion that the bioflocs aplication was able to improve the water quality shown by decreasing parameter values of TAN concentrations, ammonia, nitrite, and nitrate.